7,7′,8,8′-Tetramethoxy-4,4′-dimethyl-3,5′-bichromene-2,2′-dione - Hoong-Kun Fun; Samuel Robinson Jebas; Mehtab Parveen; Zakia Khanam; Raza Murad Ghalib (Acta Crystallographica Section E, 2009)
In the title molecule, C24H22O8, the mean planes of the two coumarin units are inclined to each other at a dihedral angle of 79.93 (3)°. The attached methoxy groups form torsion angles of 7.65 (19) and 78.36 (14)° with respect to one coumarin unit, and angles of 9.01 (16) and 99.08 (11)° with respect to the other coumarin unit. In the crystal structure, weak intermolecular C—H...O hydrogen bonds connect pairs of molecules to form dimers, generating R22(16) and R22(18) rings; the dimers are linked by further weak intermolecular C—H...O hydrogen bonds, forming extended chains. Additional stabilization is provided by weak C—H...π interactions.